Cerebral vein thrombosis in Behcet's disease - (:unkn) unknown (ELSEVIER SCIENCE INC, 2001)
Behcet's disease is a chronic, relapsing multisystem disorder, and nervous system involvement is one of the serious manifestations. Neuro-Behcet is rarely reported in children and may present with a wide variety of symptoms because the entire neuraxis may be affected. A case of cerebral vein thrombosis secondary to Behcet's disease is presented. The patient has recovered without any visual loss and had no complaints at 1-year follow-up. (C) 2001 by Elsevier Science Inc. All rights reserved.
Keywords: FAMILIAL AGGREGATION; VENOUS THROMBOSIS; NERVOUS-SYSTEM; FOLLOW-UP; INVOLVEMENT; CHILDREN; MRI